Synthesis, characterization, and semiconducting properties of π-conjugated polymers containing hydrogen-bonded bis-pyridine-thieno[3, 2-b]thiophene moieties. Issue 46 (21st November 2022) - Zhang, Bo; Ge, Congwu; Xie, Cong; Lin, Kaiwen; Yang, Wei; Liu, Bingyong; Gao, Xike; Zhou, Yinhua; Zhang, Qing
Abstract : A hydrogen bonded pyridine-thieno[3, 2- b ]thiophene-pyridine type building block TTPY has been synthesized for π-conjugated polymers and their application in organic electronic devices. Abstract : A hydrogen bonded pyridine-thieno[3, 2- b ]thiophene-pyridine type building block TTPY has been synthesized for π-conjugated polymers. The single-crystal X-ray diffraction analysis revealed that resonance-assisted hydrogen bonds (RAHBs) formed in the building block. The RAHBs and weak intramolecular noncovalent interactions together enabled a rigid co-planar structure, extended π-conjugated and a tight lamella arrangement in the solid state. Two conjugated polymers based on TTPY have also been synthesized. The PTTPY-DPP -based devices exhibited a p-type field-effect mobility of 0.17 cm 2 V −1 s −1 and the PTTPY-BDT:Y6 -based polymer solar cells showed a power conversion efficiency of 10.8%. The results demonstrated that pyridines and other azines, due to their combined electron deficiency, less steric hindrance, and especially their ability to form RAHBs, can be useful building blocks for organic semiconducting materials.